Tanggung Jawab Perdata dan Prinsip Kehati-Hatian Notaris dalam Penggunaan Artificial Intelligence yang Menimbulkan Kerugian - Caroline Cynthia; Disriani Latifah Soroinda (Syntax Corporation, 2023)
Artificial Intelligence is a technology that simulates human intelligence, programmed into electronic media to think and imitate human actions. Artificial Intelligence functions as a tool for restructuring, due diligence, and making deeds, raising concerns regarding potential errors in Artificial Intelligence output that could cause losses to legal subjects. This research examines legal responsibility when the output produced by Artificial Intelligence causes losses, with a focus on the careful application of notary principles as regulated in Article 16 of the Notary Position Law (UUJN). This research adopts a doctrinal legal research approach, utilizing secondary data from literature studies, archives, research reports, and legal sources such as UUJN and the Civil Code. Through qualitative analysis, this research reveals that Artificial Intelligence is not a legal subject but can be categorized as a tool that helps notaries. In terms of legal liability for losses caused by Artificial Intelligence, civil liability is given to the owner of the order, namely the person who uses and gives orders to Artificial Intelligence. This research emphasizes the need for careful consideration of legal responsibilities and prudence in notarial practice, along with the development of Artificial Intelligence technology in the legal domain.